203k views
3 votes
Find the limit of the formula given​

Find the limit of the formula given​-example-1

1 Answer

3 votes

Answer:


\displaystyle \lim_(x \to 0^+) x^\big{√(x)} = 1

General Formulas and Concepts:

Algebra II

  • Natural logarithms ln and Euler's number e
  • Logarithmic Property [Exponential]:
    \displaystyle log(a^b) = b \cdot log(a)

Calculus

Limits

  • Right-Side Limit:
    \displaystyle \lim_(x \to c^+) f(x)
  • Left-Side Limit:
    \displaystyle \lim_(x \to c^-) f(x)

Limit Rule [Variable Direct Substitution]:
\displaystyle \lim_(x \to c) x = c

L’Hopital’s Rule:
\displaystyle \lim_(x \to c) (f(x))/(g(x)) = \lim_(x \to c) (f'(x))/(g'(x))

Differentiation

  • Derivatives
  • Derivative Notation

Basic Power Rule:

  1. f(x) = cxⁿ
  2. f’(x) = c·nxⁿ⁻¹

Explanation:

We are given the following limit:


\displaystyle \lim_(x \to 0^+) x^\big{√(x)}

Substituting in x = 0 using the limit rule, we have an indeterminate form:


\displaystyle \lim_(x \to 0^+) x^\big{√(x)} = 0^0

We need to rewrite this indeterminate form to another form to use L'Hopital's Rule. Let's set our limit as a function:


\displaystyle y = \lim_(x \to 0^+) x^\big{√(x)}

Take the ln of both sides:


\displaystyle lny = ln \Big( \lim_(x \to 0^+) x^\big{√(x)} \Big)

Rewrite the limit by including the ln in the inside:


\displaystyle lny = \lim_(x \to 0^+) ln \big( x^\big{√(x)} \big)

Rewrite the limit once more using logarithmic properties:


\displaystyle lny = \lim_(x \to 0^+) √(x)ln(x)

Rewrite the limit again:


\displaystyle lny = \lim_(x \to 0^+) (ln(x))/((1)/(√(x)))

Substitute in x = 0 again using the limit rule, we have an indeterminate form in which we can use L'Hopital's Rule:


\displaystyle \lim_(x \to 0^+) (ln(x))/((1)/(√(x))) = (\infty)/(\infty)

Apply L'Hopital's Rule:


\displaystyle \lim_(x \to 0^+) (ln(x))/((1)/(√(x))) = \lim_(x \to 0^+) \frac{(1)/(x)}{\frac{-1}{2x^\big{(3)/(2)}}}

Simplify:


\displaystyle \lim_(x \to 0^+) \frac{(1)/(x)}{\frac{-1}{2x^\big{(3)/(2)}}} = \lim_(x \to 0^+) -2√(x)

Redefine the limit:


\displaystyle lny = \lim_(x \to 0^+) -2√(x)

Substitute in x = 0 once more using the limit rule:


\displaystyle \lim_(x \to 0^+) -2√(x) = -2√(0)

Evaluating it, we have:


\displaystyle \lim_(x \to 0^+) -2√(x) = 0

Substitute in the limit value:


\displaystyle lny = 0

e both sides:


\displaystyle e^\big{lny} = e^\big{0}

Simplify:


\displaystyle y = 1

And we have our final answer.

Topic: AP Calculus AB/BC (Calculus I/I + II)

Unit: Limits

User George G
by
5.7k points